Workshop Pembuatan Video Pembelajaran Interaktif Menggunakan Microsoft Powerpoint Dan Editing Menggunakan Video Editor - Imelda Saluza; Dewi Sartika; Indah Permata Sari; Yosef Yulius (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
PKM activities are carried out to improve teacher knowledge and skills regarding learning media, in this case interactive learning videos. And more specifically, there is an increase in teacher creativity in designing learning media so that they become interactive media that can be used for the learning process. The method used in the implementation of this PKM is in the form of lectures, demonstrations (simulations), and practices which are followed by 33 teachers at SMP Negeri 30 Palembang. This activity includes three stages, namely, observation with the aim of knowing the initial conditions of the school that will be given this activity. Based on the observations, it was found that most of the teachers at SMP Negeri 30 Palembang find it difficult to cope with the different levels of understanding of students and the media that can be used for repetitive learning. Then proceed to the second stage by sharing knowledge between the team and the teacher and the last stage evaluating the activities that have been carried out. Based on the results of the evaluation, it can be concluded that the activities carried out are able to increase the knowledge and skills of teachers in making interactive learning videos, this is indicated by the number of teachers whose knowledge increases by 30 people and will use them as learning media as many as 30 people.